PENGEMBANGAN SENSOR WARNA BERBASIS ARDUINO UNTUK DETEKSI WARNA KARET RSS - Sihabuddin, Aspina; Yudhiakto Pramudya (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
The quality of rubber products, particularly Ribbed Smoked Sheet (RSS), is crucial for Indonesia's automotive industry. Currently, quality assessment at PT KMS Rubber Factory relies on visual inspection, leading to subjective and inconsistent results. To address this, this study developed an RRS color detection system using a TCS3200 sensor and Arduino. The research followed a waterfall methodology, with testing conducted at Ahmad Dahlan University and PT KMS using RRS samples of varying quality. Results showed that the TCS3200 sensor effectively detected color variations with reasonable accuracy, though unstable lighting conditions affected performance. The use of a black box significantly minimized external light interference. Additionally, the study revealed that the factory’s RRS quality was actually categorized as RRS 2 and RRS 3, contrary to workers' visual assessment, which had classified it as RRS 1. This system offers an efficient solution for the rubber industry, particularly for small producers and farmers, to enhance quality control. Furthermore, the device serves as a practical educational tool for learning about color, light, and sensor technology. Thus, this innovation has strong potential to improve rubber product quality and production efficiency in Indonesia.